Canadian Stroke Best Practice Recommendations: Rehabilitation, Recovery, and Community Participation following Stroke. Part Two: Transitions and Community Participation Following Stroke. Issue 7 (October 2020) - Mountain, Anita; Patrice Lindsay, M; Teasell, Robert; Salbach, Nancy M; de Jong, Andrea; Foley, Norine; Bhogal, Sanjit; Bains, Naresh; Bowes, Rebecca; Cheung, Donna; Corriveau, Helene; Joseph, Lynn; et al.
The sixth update of the Canadian Stroke Best Practice Recommendations for Transitions and Community Participation following Stroke is a comprehensive set of evidence-based guidelines addressing issues faced by people following an acute stroke event. Establishing a coordinated and seamless system of care that supports progress achieved during the initial recovery stages throughout the transition to the community is more essential than ever as the medical complexity of people with stroke is also on the rise. All members of the health-care team engaged with people with stroke, their families, and caregivers are responsible for partnerships and collaborations to ensure successful transitions and return to the community following stroke. These guidelines reinforce the growing and changing body of research evidence available to guide ongoing screening, assessment, and management of individuals following stroke as they move from one phase and stage of care to the next without "falling through the cracks." It also recognizes the growing role of family and informal caregivers in providing significant hours of support that disrupt their own lives and responsibilities and addresses their support and educational needs. According to Statistics Canada, in 2012, eight million Canadians provided care to family members or friends with a long-term health condition, disability, or problems associated with aging. These recommendations incorporate aspects that were previously in the rehabilitation module for the purposes of streamlining, and both modules should be reviewed in order to provide comprehensive care addressing recovery and community reintegration and participation. These recommendations cover topics related to support and education of people with stroke, families, and caregivers during transitions and community reintegration. They include interprofessional planning and communication, return to driving, vocational roles, leisure activities and relationships and sexuality, and transition to long-term care.